2018
DOI: 10.1002/dac.3713
|View full text |Cite
|
Sign up to set email alerts
|

A cost‐effective attack matrix based key management scheme with dominance key set for wireless sensor network security

Abstract: Summary To guarantee the proper functionality of wireless sensor network even in the presence of the potential threats, a well‐designed key management scheme is very important. The assumptions about attackers critically influence the performance of security mechanisms. This paper investigates the problem of node capture from adversarial view point in which the adversary intelligently exploits the different vulnerabilities of the network to establish a cost‐effective attack matrix. To counteract such attacks, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It is shown that to maintain same connectivity, the proposed scheme requires lesser key ring size. A dominance rank based KMS is proposed in [54] that consider the key compromise probability to increase the security of resulting scheme.…”
Section: (Ix) Hybrid Schemesmentioning
confidence: 99%
“…It is shown that to maintain same connectivity, the proposed scheme requires lesser key ring size. A dominance rank based KMS is proposed in [54] that consider the key compromise probability to increase the security of resulting scheme.…”
Section: (Ix) Hybrid Schemesmentioning
confidence: 99%